Evaluation of a general practitioner with special interest service for dermatology: randomised controlled trial. Issue 7530 (6th December 2005) - Salisbury, Chris; Noble, Alison; Horrocks, Sue; Crosby, Zoe; Harrison, Viv; Coast, Joanna; de Berker, David; Peters, Tim
Abstract: Objective To assess the effectiveness, accessibility, and acceptability of a general practitioner with special interest service for skin problems compared with a hospital dermatology clinic. Design Randomised controlled trial. Setting General practitioner with special interest dermatology service and hospital dermatology clinic. Participants Adults referred to a hospital dermatology clinic and assessed by a consultant or the general practitioner with special interest service, . Suitable patients had non-urgent skin problems and had been identified from the referral letter as suitable for management by a general practitioner with special interest. Interventions Participants were randomised in 2:1 ratio to receive management by a general practitioner with special interest or usual hospital outpatient care. Main outcome measures Primary outcomes were disease related quality of life (dermatology life quality index) and improvement in patients' perception of access to services, assessed nine months after randomisation. Secondary outcomes were patient satisfaction, preference for site of care, proportion of failed appointments, and waiting times to first appointment. Results 49% of the participants were judged suitable for care by the general practitioner with special interest service. Of 768 patients eligible, 556 (72.4%) were randomised (354 to general practitioner with special interest, 202 to hospital outpatient care). After nine months, 422 (76%) were followed up. No noticeable differences were found between the groups in clinical outcome (median dermatology life quality index score = 1 both arms, ratio of geometric means 0.99, 95% confidence interval 0.85 to 1.15). The general practitioner with special interest service was more accessible (difference between means on access scale 14, 11 to 19) and waited a mean of 40 (35 to 46) days less. Patients expressed slightly greater satisfaction with consultations with a general practitioner with special interest (difference in mean satisfaction score 4, 1 to 7), and at baseline and after nine months 61% said they preferred care at the service. Conclusions The general practitioner with special interest service for dermatology was more accessible and preferred by patients than hospital outpatient care, achieving similar clinical outcomes. Trial registration ISRCTN31962758 .